PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYA PADA RUMAH SAKIT UMUM KABANJAHE - LASRIDA SIGALINGGING (JURNAL ILMIAH MAKSITEK, 2020)
Work environment is everything around employees who can influence the employees in carrying out the tasks that are sacrificed by the company. And work productivity is something that can be dictated by the spirit and work discipline of the employees in completing every task he has to offer, always based on the method of work or methods that have been established so that it will By the satisfactory results of work. A good working environment is needed to improve the productivity of employees ' work at the Kabanjahe General Hospital. So researchers are interested in researching part of the working environment towards employee work productivity. The respondent used to complement the study was a clerk of the Kabanjahe General Hospital. In this research researchers use multiple linear regression analyses, using partial hypothesis tests or t tests and also using coefficient of determination (R2) tests.Based on simple regression equations, the work environment has a positive regression coefficient that proves its contribution to working productivity at the Kabanjahe General Hospital. This suggests that the working environment can affect the productivity of work at the Kabanjahe General Hospital.Based on the partial hypothesis test or T-Test obtained then reject Ho and receive H1 for the working environment variable. Thus, a partial working environment is positively influential with a significant degree of influence on work productivity against the Kabanjahe General Hospital. Based on the partial hypothesis test or T-Test obtained then reject Ho and receive H1 for the working environment variable. Thus, a partial working environment is positively influential with a significant degree of influence on work productivity against the Kabanjahe General Hospital.Based on coefficient of determination (R2), the value of the coefficient of determination is 0.484. This suggests that the ability of the Working environment variable (X) explains its influence on the working productivity variables of the Kabanjahe General Hospital by 48.4%. The remaining 51.6% is the influence of other free variables not examined in this study, such as working discipline, corporate culture, and employee commitment.